Evolution of optical nonlinearity within a graphene/Bi2Te3 heterostructure. Issue 23 (26th May 2022) - Lan, Jia-Chi; Yang, Chan-Shan; Chen, Chun-Hu; Cheng, Cheng-Maw; Liu, Hong; Lee, Chao-Kuei
Abstract : Effect of passive Q -switched solid-state laser for different absorption behaviours of absorbers. Abstract : A z -scan technique was used to analyse the optical nonlinearity of a graphene/Bi2 Te3 heterostructure under pulsed laser excitation at 800 nm. The intensity-dependent transmittance over 10 orders of magnitude indicated that the heterostructure displayed a versatile nonlinear absorption behaviour. The sign change of the nonlinear refractive index n 2 at a high optical intensity from the saturable absorption of the Bi2 Te3 surface state was investigated. Meanwhile, the relationship between the nonlinear absorption and laser output was discussed and used to interpret the laser behaviour variation with an increase in pump power. Our work provides an understanding of the optical nonlinearity evolution and a scaling guide for quality solid-state lasers.